2022
DOI: 10.1200/op.22.00224
|View full text |Cite
|
Sign up to set email alerts
|

Better Late Than Never: Fully Incorporating Oncology Advanced Practice Providers Into Cancer Clinical Trials

Abstract: Author affiliations and support information (if applicable) appear at the end of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…APPs can identify eligible patients from their clinical practice and collaborate on confirming eligibility criteria and assist with baseline studies. 5,6,19,20 Almost all practices reporting APP involvement in research activities reported that APPs were involved in clinical trial visits. As previous survey results and literature have shown, to date, the primary role of the APP in clinical research has been providing clinical care for patients on trials.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…APPs can identify eligible patients from their clinical practice and collaborate on confirming eligibility criteria and assist with baseline studies. 5,6,19,20 Almost all practices reporting APP involvement in research activities reported that APPs were involved in clinical trial visits. As previous survey results and literature have shown, to date, the primary role of the APP in clinical research has been providing clinical care for patients on trials.…”
Section: Discussionmentioning
confidence: 99%
“…As previous survey results and literature have shown, to date, the primary role of the APP in clinical research has been providing clinical care for patients on trials. [4][5][6][7][8] By contrast, several areas for improvement still exist for integrating APPs in clinical research. Only 43% of practices reported that APPs are involved in presenting and discussing clinical trials to patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations